Typification of seven names of Sorbus (Rosaceae) from China - Chen, Xin (Phytotaxa, 2016)
Sorbus Linnaeus (1753: 477) in its broad sense contains 100–250 species mainly distributed in temperate regions of the Northern Hemisphere, with 67 species in China (Phipps et al. 1990, Lu & Spongberg 2003, Kalkman 2004). In the course of taxonomic revision of Chinese Sorbus, typification of the following seven names is conducted or discussed here so that application of these names can be stabilized.